Effects of meperidine or saline on thermal, mechanical and electrical nociceptive thresholds in cats - Millette, Valerie M.; Steagall, Paulo V. M. [UNESP]; Duke-Novakovski, Tanya; Livingston, Alex J. (Wiley-Blackwell, 2008)
Objective To measure cutaneous electrical nociceptive thresholds in relation to known thermal and mechanical stimulation for nociceptive threshold detection in cats.Study design Prospective, blinded, randomized cross-over study with 1-week washout interval.Animals Eight adult cats [bodyweight 5.1 +/- 1.8 kg (mean + SD)].Methods Mechanical nociceptive thresholds were tested using a step-wise manual inflation of a modified blood pressure bladder attached to the cat's thoracic limb. Thermal nociceptive thresholds were measured by increasing the temperature of a probe placed on the thorax. The electrical nociceptive threshold was tested using an escalating current from a constant current generator passed between electrodes placed on the thoracic region. A positive response (threshold) was recorded when cats displayed any or all of the following behaviors: leg shake, head turn, avoidance, or vocalization. Four baseline readings were performed before intramuscular injection of meperidine (5 mg kg(-1)) or an equal volume of saline. Threshold recordings with each modality were made at 15, 30, 45, 60, 90, and 120 minutes post-injection. Data were analyzed using ANOVA and paired t-tests (significance at p < 0.05).Results There were no significant changes in thermal, mechanical, or electrical thresholds after saline. Thermal thresholds increased at 15-60 minutes (p < 0.01) and mechanical threshold increased at 30 and 45 minutes after meperidine (p < 0.05). Maximum thermal threshold was +4.1 +/- 0.3 degrees C above baseline at 15 minutes while maximum mechanical threshold was 296 +/- 265 mmHg above baseline at 30 minutes after meperidine. Electrical thresholds following meperidine were not significantly different than baseline (p > 0.05). Thermal and electrical thresholds after meperidine were significantly higher than saline at 30 and 45 minutes (p < 0.05), and at 120 minutes (p < 0.05), respectively. Mechanical thresholds were significantly higher than saline treatment at 30 minutes (p <= 0.05).Conclusion and clinical relevance Electrical stimulation did not detect meperidine analgesia whereas both thermal and mechanical thresholds changed after meperidine administration in cats.
Keywords: analgesia; cat; electrical; mechanical; thermal; thresholds